STRATEGI ADAPTASI ORANG TUA TUNGGAL-IBU- DALAM PEMENUHAN KEBUTUHAN KELUARGA (STUDI KASUS DI DESA BUKIT GAJAH KECAMATAN UKUI KABUPATEN PELALAWAN) - Hardiani, Dewi Nurul; Yusuf, Yusmar (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
Being a single parent—Mother- a phenomenon is a phase not experienced by everyone, a change in the function and role of a person before and when being a single parent- can affect changes in the economy, social, and a psychology . The single parent –mother- should replace the role of the father as head of the household in some aspects such as the decision maker, and make a living. Need process of being able to go through a period of darkness or sadness, and single parent or single mother who divorced or abandoned his partner experienced social pressure they must accept such as financial problems, feeling lonely because they are used to being alone, dealing with negative think , accept the present reality alone, even work to earn a living in order to meet the needs of his life and his children that he bear. phenomenon is observed this time been located in Bukit Gajah village District of Ukui Pelalawan Regency where the area has the characteristics of informants in accordance with the subject under study. The research data is collected by interview, observation and documentation. The interview was a structured interview in which the researcher first prepared the interview guidelines. The present research aims to identify what are the driving and inhibiting factors in being a single parent –Mother- and how to structure a strategy and adapt to new and advanced circumstances for their children .Keywords: Single Parent , Mother, Adaptation Strategy .